Pups speak up - Meltzer, Maxine; Schmidt, Karen (New York : Bradbury Press : Maxwell Macmillan International, 1994)
Dog characters in different countries introduce the words for "hello" in the languages native to those countries.
School Library Journal.
3.5
K-3
Keywords: Polyglot glossaries, phrase books, etc. -- Juvenile literature; Salutations -- Juvenile literature; Polyglot glossaries, phrase books, etc; Salutations; Vocabulary; Polyglot dictionaries; Vocabulary; Polyglot glossaries, phrase books, etc; Salutations; Vocabulary